EKSPLORASI KEARIFAN LOKAL KHAS BORNEO: BIOSINTESIS NANOPARTIKEL PERAK EKSTRAK ETANOL DAUN KOKANG (Lepishanthes amoena (Hass) Leenh) - Aminah; Rahman, Nurul Aulia; Amalia, Sindi; Hardiani, Lia; Khairunnisa, Annida; Jubaidah, Siti; Puspita, Alfiana Dwi (Jurnal Riset Kefarmasian Indonesia, 2024)
Biosynthesis of silver nanoparticles (AgNP) is a process of changing Ag+ ions to Ag0. The biosynthesis method in this research is green synthesis using natural ingredients to reduce silver, this synthesis is safer, environmentally friendly and economical. Based on this, this research aims to determine the optimal reaction conditions in the biosynthesis process using ethanol extract from cock leaves. The research method carried out pH optimization with variations of 8, 9, and 10 and then obtained the best pH, where the pH optimization will later be used in the AgNO3 optimization process with variations of 1mM, 2mM, and 4mM. After obtaining the best Ag optimization, the next stage was extract optimization using variations of 0.5%, 1% and 2%, the results of which will be seen based on the SPR peak of 400-500 nm which indicates the formation of AgNPs. The results of the research showed that AgNPs from cockang leaf ethanol extract were able to reduce at pH 8, AgNO3 2mM and 4mM, as well as 0.5% extract, and the contact time reaction showed a good formula for AgNP 1, AgNP2, AgNP3 which was indicated by the absorbance intensity at long waves that form AgNPs at the SPR peak of 400-500. Based on the results of SEM characterization, the morphology at a concentration of 2 mM has a surface that is not very smooth and the size is not very uniform, but at a concentration of 4 mM the surface is smooth and the particles are not uniform. With particle sizes in the range of 50-80 nm.